A Verifiably Secure ECC Based Authentication Scheme for Securing IoD Using FANET - Saeed Ullah, Jan; Irshad Ahmed, Abbasi; Fahad, Algarni; Adnan, Shahid Khan (IEEE, 2022)
Perfect forward secrecy, cross-verification, and robust mutual authentication guarantee secure communication through unfavorable and unsafe channels. The speedy development in wireless communication and drone-assisted networking technology has miserable significance in many areas, including wildlife monitoring, sidewalk checking, infrastructure inspection, and smart city surveillance. But guaranteeing message integrity, non-repudiation, authenticity, and authorization for information transmission for these areas are still challenging for researchers when using Flying Ad Hoc Networks (FANETs). The FANET’s existence for drone technology is more complicated due to dynamic changes in its topology and easily vulnerable to the adversary for numerous attacks. So far, before exhilarating a drone in the Internet-ofDrones (IoD) environment, controlled layered network architecture is indispensable to allow only legitimate drones to collaborate securely with each other and with the ground control station (GCS) for building the highest trust. A minor lapse creates a severe complication for communication security because an attacker might be trapping data from the open network channel and using it for their unusual deeds. Attentively, identification authentication and message authentication are necessary for such a sensitive environment. Therefore, in this research article, we have designed a verifiably secure Elliptic Curve Cryptographic (ECC)- based authentication scheme for IoD using FANET. The formal security proof of the scheme has been made using a programming verification toolkit ProVerif2.03, Random Oracle Model (ROM), and informally by pragmatic illustration. And the performance evaluation section of the article has been made by considering storage, computation, and communication costs. When comparing the proposed security mechanism with state-of-the-art schemes, it has been shown that the work done in this article is efficient and effective and is suitable for practically implementing in the IoD environment.